1970
DOI: 10.1021/bi00828a009
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of the protein component of tissue factor

Abstract: Tissue factor is a particle-bound lipoprotein which initiates coagulation uia the extrinsic system. The present study presents a modification and extension of previous techniques by which 40 mg of soluble tissue factor can be prepared from 100 g of lung acetone powders with 800-to 1500-fold purification. Although the purified protein contains 7z residual phospholipid, recombination with 7.5 mg of phospholipid per mg of protein is required for maximal coagulant activity; this lipid to protein ratio stimulates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 13 publications
5
26
0
Order By: Relevance
“…Accumulating evidence suggests that tissue factor is a glycoprotein derived from plasma membrane: (a) purified tissue factor contains carbohydrate (1); (b) tissue factor antigen is found on the cell surface (2, 3); (c) tissue factor activity has been localized histochemically to the plasma membrane (4); (d) tissue factor activity can be stripped from cells in culture without loss of intracellular material (5). We now report another observation consistent with previous data: concanavalin A (con A) 1 inhibits the coagulant activity of purified tissue factor.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Accumulating evidence suggests that tissue factor is a glycoprotein derived from plasma membrane: (a) purified tissue factor contains carbohydrate (1); (b) tissue factor antigen is found on the cell surface (2, 3); (c) tissue factor activity has been localized histochemically to the plasma membrane (4); (d) tissue factor activity can be stripped from cells in culture without loss of intracellular material (5). We now report another observation consistent with previous data: concanavalin A (con A) 1 inhibits the coagulant activity of purified tissue factor.…”
Section: Introductionsupporting
confidence: 92%
“…We have previously demonstrated that tissue factor apoprotein stains positively for carbohydrate in acrylamide gels, suggesting a glycoprotein nature (1). Furthermore, the lipophilic nature of the molecule is consonant with membrane constituents, evidence which has been substantiated by antigenic localization (2,3) and factor VII binding sites (4).…”
Section: Discussionmentioning
confidence: 95%
“…The rabbit antibody neutralized tissue factor from human brain and placenta. Two precipitin lines appeared on immunodiffusion plates; these probably correspond to the two species previously noted (42). The rabbit antibody neutralized coagulant activity of human brain acetone powders or purified placental tissue factor.…”
Section: Methodsmentioning
confidence: 52%
“…Active fractions, as determined by the assay previously described (41), were pooled and rechromatographed on Sepharose 6B. Criteria for purity are detailed in the original reference (42). The placental tissue factor had a specific activity of 10,000 U of tissue factor/mg protein.…”
Section: Methodsmentioning
confidence: 99%
“…All the procedures were carried out at 4°C. Placental phospholipid was extracted by a modification of the method of Nemerson and Pitlick (1970). A placenta frozen at -40°C was thawed and washed in 0.15 M NaCI followed by removal of the umbilical cord and amniotic membrane.…”
Section: Isolation Of Cpb IIImentioning
confidence: 99%